Stakeholder Analysis in the Management of the Aek Silang Mini-Hydro Power Plant (PLTM) in Humbang Hasundutan Regency - Oktalia, Oktalia; Aisyah, Dara (SAJJANA: Public Administration Review, 2026)
Purpose: This study aims to analyze stakeholders in the management of the Aek Silang II Mini Hydropower Plant (MHPP) in Humbang Hasundutan Regency by identifying the stakeholders involved, categorizing their levels of influence and interest, and mapping the relationships among stakeholders. Methodology: This study employed a descriptive qualitative approach with a single-case study design. Data were collected through semi-structured interviews, field observations, and document analysis. The data were analyzed using the stakeholder analysis framework proposed by Reed et al. (2009), as cited in Sentanu et al. (2024), which includes stakeholder identification, the power–interest matrix, and the Actor Linkage Matrix (ALM). Findings: The study identified eleven stakeholders involved in the management of the Aek Silang II Mini Hydropower Plant. PT Bakara Energi Lestari (PT BEL) was identified as the most dominant Key Player and exhibited the greatest stakeholder management deficit due to its limited community engagement and inadequate implementation of corporate social responsibility (CSR). Farming communities were categorized as Subjects, reflecting high interest but low influence. Stakeholder relationships were predominantly characterized by conflict resulting from weak communication and ineffective grievance mechanisms, while strong collaboration was found only among stakeholders bound by formal contractual arrangements. Social Implications: The study recommends that PT BEL develop formal stakeholder management and CSR guidelines, strengthen government oversight, and establish institutionalized community participation mechanisms to promote more inclusive and sustainable MHPP management.